TAPAS-360°: A Tool for the Design and Experimental Evaluation of 360° Video Streaming Systems - Giuseppe Ribezzo; Luca De Cicco; Vittorio Palmisano; Saverio Mascolo (Proc. of the 28th ACM International Conference on Multimedia, 2020)
Video streaming platforms are required to innovate their delivery pipeline to allow new and more immersive video content to be supported. In particular, Omnidirectional videos enable the user to explore a 360° scene by moving their heads using Head Mounted Display devices. Viewport adaptive streaming allows changing dynamically the quality of the video falling in the user’s field of view. In this paper, we present TAPAS-360°, an open-source tool that enables designing and experimenting all the components required to build omnidirectional video streaming systems. The tool can be used by researchers focusing on the design of viewport-adaptive algorithms and also to produce video streams to be employed for subjective and objective Quality of Experience evaluations.
Keywords: dash; adaptive video streaming; 360-degree video